Cis-encoded non-coding antisense RNAs in streptococci and other low GC Gram (+) bacterial pathogens - Cho, Kyu Hong; Kim, Jeong-Ho (Frontiers in Genetics, 2015)
Due to recent advances of bioinformatics and high throughput sequencing technology, discovery of regulatory noncoding RNAs in bacteria has been increased to a great extent. Based on this bandwagon, many studies searching for trans-acting small noncoding RNAs in streptococci have been performed intensively, especially in the important human pathogen, group A and B streptococci. However, studies for cis-encoded noncoding antisense RNAs in streptococci have been scarce. A recent study shows antisense RNAs are involved in virulence gene regulation in group B streptococcus, S. agalactiae. This suggests antisense RNAs could have important roles in the pathogenesis of streptococcal pathogens. In this review, we describe recent discoveries of chromosomal cis-encoded antisense RNAs in streptococcal pathogens and other low GC Gram (+) bacteria to provide a guide for future studies.